(3CSS GdJShjb GdMOjKs - (3eMeO YHO GdYXje(B, (3CHh GdfLGs ((3GdGScfOQjI(B:s (3GdOGQ GdLGeYjI(B,s, 2011)
(3fXQI YGeI Ydi GdJShjb , JbSje GdShb Gdi bWGYGJ h JMOjO GdShb GdSJgOa h HfGA GdeQcR GdPgfj ddefJL , fXe GdeYdheGJ GdJShjbjI h HMhK GdJShjb , Sdhc GdeSJgdc hCShGb GdGYeGd h GdSdhc GdTQGFj deTJQj GdCYeGd , GdefJL , GdJSYjQ , GdGJUGdGJ GdJShjbjI , bfhGJ GdJhRjY h CNjQG GdJShjb GdGdcJQhfj(B.s
Keywords: (3COGQI GdeHjYGJs; (3GdJShjbs; (3GdJShjb(B- (3JcfhdhLjGs